In vitroâ€in vivo performance evaluation of treated Plantago ovata husk based fast dissolving tablets of glipizide: Flashtab technology - Jha, Asst. Prof. Antesh Kumar (Asian Journal of Pharmaceutics (AJP), 2014)
Physicians suggest premeal administration of glipizide (30 min before a meal) because of longer disintegration time (approximately 15 min) of conventional tablet. Hence, the dosage form was developed, called as fast dissolvingÂ tablet (FDT), which disintegrates rapidly within a minute. FDTs by Flashtab technology is based on a swellable agent andÂ a superdisintegrant. In the current study, treated Plantago ovata husk (TPOH), and microcrystalline cellulose were utilizedÂ as natural superdisintegrant and swellable agent, respectively. FDT formulations were prepared by direct compression andÂ evaluated for in vitro tablet performance, such as disintegration time, wetting time, hardness, friability, swelling and percentÂ drug release. On the basis of finding, formulation with 15% TPOH concentration (TPOH 7) was selected as optimizedÂ formulation. To evaluate the in vitro performance, the formulation TPOH 7 and the marketed tablets (glynase) wereÂ administered to rabbits. In the case of marketed tablet, the peak plasmaâ€concentration of glipizide was obtained in 2.83 h ofÂ administration whereas it was 2 h for TPOH 7 indicating immediate absorption and therefore faster onset of action of the prepared FDT formulation than the marketed one. Drug interaction studies, performed by using FTIR spectroscopy, Xâ€rayÂ diffractometry and differential scanning calorimetric methods, indicate that the glipizide is compatible with the formulationÂ components. The accelerated stability study (40Â°C Â± 2Â°C/75% Â±5% relative humidity) for the optimized formulationÂ showed a negligible change over time for the in vitro parameters. The results suggest that TPOH has promising potential forÂ faster disintegration and fulfills the requirement of FDTs. Key words: Direct compression, fast dissolving tablets, flashtab technology, glipizide, Plantago ovata husk, superdisintegrant